Real effects of the audit choice - Kausar, Asad (2016)
We hypothesize that the choice to obtain a financial statement audit provides external financiers with incremental information about the firm, which helps reduce information asymmetry and financing frictions. Using a natural experiment, we show that when external financiers observe a firm׳s choice to voluntarily obtain an audit, the firms obtaining an audit significantly increase their debt, investment, and operating performance, and become more responsive to their investment opportunities. Further, we find that these effects are stronger for firms that are financially constrained and weaker for firms with other means to reduce financing frictions. Overall, our evidence suggests that the audit choice conveys information to capital providers, which reduces financing frictions and improves performance.